Pregnancy Outcomes on Chronically Hemodialyzed Women in Arab World: A Systematic Review - Leena Mohamed Khonji; Hussein AlHafnawi; Zohour Ibrahim Rashwan; Gayathripriya Narayanan; Nandini Mannadath; Magda Mohamed Bayoumi (International Journal of Midwifery Nursing And Practices, 2024)
Pregnancy carries a major risk of difficulties, as highlighted by the present systemic study on pregnancy outcomes in persistently hemodialyzed women in the Arab world. The objective of this systematic review was to describe the pregnancy outcomes among chronically hemodialyzed pregnant women in Arab countries in terms of the incidence of pregnancy among women on maintenance hemodialysis and the incidence of maternal and fetal complications of pregnant women on hemodialysis. A systematic review was performed based on PRISMA guidelines. Data searches were conducted through databases such as MEDLINE, and Scopus, and manual search of multiple databases. 11 studies met the inclusion criteria after applying a filtering approach, which was ready for analysis. Results indicated that the included studies reported 302 pregnancies with a success rate of 43.4%. The mean yearly incidence rate of pregnancy among women was 1.12%. The most common complications reported were abortion for mothers and IUFR for fetuses (7.7%). The main recommendation was to increase the duration and the frequency of HD, as it is reported in four articles to be associated with a higher success rate with statistical significance (p-value<0.05).
Keywords: Chronic kidney disease; End Stage Renal Disease; Fetal outcome; Pregnancy outcome; hemodialysis